GPS network noise analysis: a case study of data collected over an 18-month period. Issue 2 (2nd July 2016) - Nistor, Sorin; Buda, Aurelian Stelian
Abstract : For the error analysis of the GPS velocity component we have to consider many factors, including the determination of the stochastic model. In this article we intended to analyse the results obtained by using data gathered during a period of 18 months. The presence of the noise contained within the GPS station coordinate time series is recommended to be fitted by using a linear trend to the coordinate's time series and after this procedure to model the noise properties of the residuals. For the noise determination we used a first-order Gauss-Markov model – FOGM. To see the behaviour of the chosen noise model, we used the power spectra density of the residuals and the log likelihood values and we compared the results with those from the power law plus white noise model. In the estimation process we used the semiannual sinusoidal signal to express the seasonal influence. The amplitudes and phase lag of the seasonal variation were also computed. Although the noise that has a large contribution in a relatively short data span – shorter than 2.5 years – is considered to be white noise, using the average we have shown that the presence of coloured noise has to be taken into account.